Y5F3[AsO3]4 and Y5Cl3[AsO3]4: Two Non-Isostructural Yttrium Halide Oxoarsenates(III) and Their Potential as Hosts for Luminescent Eu3+- and Tb3+-Doping - Ralf J. C. Locke; Martina Mikuta; Florian Ledderboge; Frank C. Zimmer; Henning A. Höppe; Thomas Schleid (Crystals)
Y5F3[AsO3]4 crystallizes needle-shaped in the tetragonal space group P4/ncc with the lattice parameters a = 1143.80(8) pm, c = 1078.41(7) pm and c/a = 0.9428 for Z = 4. The yttrium-fluoride substructure linked via secondary contacts forms a three-dimensional network <semantics><mtable><mtr><mtd>3</mtd></mtr><mtr><mtd>∞</mtd></mtr></mtable></semantics>{[Y5F3]12+} and the remaining part consists of ψ1-tetrahedral [AsO3]3− units, which leave lone-pair channels along [001]. In contrast, platelet-shaped Y5Cl3[AsO3]4 crystals adopt the monoclinic space group C2/c with the lattice parameters a = 1860.56(9) pm, b = 536.27(3) pm, c = 1639.04(8) pm and β = 105.739(3)° for Z = 4. Condensation of [(Y1,2)O8]13− polyhedra via four common edges each leads to fluorite-like <semantics><mtable><mtr><mtd>2</mtd></mtr><mtr><mtd>∞</mtd></mtr></mtable></semantics> {[(Y1,2)O <semantics><mtable><mtr><mtd>e</mtd></mtr><mtr><mtd>8/2</mtd></mtr></mtable></semantics> ]5−} layers spreading out parallel to the (100) plane. Their three-dimensional linkage occurs via the (Y3)3+ cations with their Cl− ligands on the one hand and the As3+ cations with their lone-pairs of electrons on the other, which also form within [AsO3]3− anions lone-pair channels along [010]. Both colorless compounds can be obtained by solid-state reactions from corresponding mixtures of the binaries (Y2O3, As2O3 and YX3 with X = F and Cl) at elevated temperatures of 825 °C, most advantageously under halide-flux assistance (CsBr for Y5F3[AsO3]4 and ZnCl2 for Y5Cl3[AsO3]4). By replacing a few percent of YX3 with EuX3 or TbX3, Eu3+- or Tb3+-doped samples are accessible, which show red or green luminescence upon excitation with ultraviolet radiation.